ETIKA DAN KEAMANAN DATA PADA AI GENERATIF UNTUK TUGAS SEKOLAH - Kahfi Heryandi Suradiraja; Mardiyanto; Niki Ratama (Abdi Jurnal Publikasi, 2026)
The development of generative Artificial Intelligence (AI) technology has had a significant impact on education, particularly in assisting students with school assignments. However, the use of AI without proper understanding of ethics and data security may lead to various issues, such as plagiarism, technology dependency, and risks of personal data leakage. This Community Service activity aimed to improve students’ understanding of ethical AI usage and the importance of digital data security. The activity was conducted over three days at SMA Al Wafi Islamic Boarding School using lecture, discussion, demonstration, and hands-on practice methods. The results showed that participants gained better understanding regarding responsible AI usage. In addition, this activity successfully developed a web-based application called “AI Ethics Checker for Assignments” to help students independently evaluate the ethical use of AI in school assignments. The application includes text checking, AI ethics checklists, paraphrasing suggestions, and digital data security education features. In the future, the application can be further developed using Fuzzy Logic, Machine Learning, and Deep Learning methods to improve the intelligence and accuracy of analysis. This activity is expected to encourage ethical, secure, and responsible AI usage culture in educational environments.